3x-4(5-2x)=2x-(3x-9)

Simple and best practice solution for 3x-4(5-2x)=2x-(3x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-4(5-2x)=2x-(3x-9) equation:


Simplifying
3x + -4(5 + -2x) = 2x + -1(3x + -9)
3x + (5 * -4 + -2x * -4) = 2x + -1(3x + -9)
3x + (-20 + 8x) = 2x + -1(3x + -9)

Reorder the terms:
-20 + 3x + 8x = 2x + -1(3x + -9)

Combine like terms: 3x + 8x = 11x
-20 + 11x = 2x + -1(3x + -9)

Reorder the terms:
-20 + 11x = 2x + -1(-9 + 3x)
-20 + 11x = 2x + (-9 * -1 + 3x * -1)
-20 + 11x = 2x + (9 + -3x)

Reorder the terms:
-20 + 11x = 9 + 2x + -3x

Combine like terms: 2x + -3x = -1x
-20 + 11x = 9 + -1x

Solving
-20 + 11x = 9 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-20 + 11x + x = 9 + -1x + x

Combine like terms: 11x + x = 12x
-20 + 12x = 9 + -1x + x

Combine like terms: -1x + x = 0
-20 + 12x = 9 + 0
-20 + 12x = 9

Add '20' to each side of the equation.
-20 + 20 + 12x = 9 + 20

Combine like terms: -20 + 20 = 0
0 + 12x = 9 + 20
12x = 9 + 20

Combine like terms: 9 + 20 = 29
12x = 29

Divide each side by '12'.
x = 2.416666667

Simplifying
x = 2.416666667

See similar equations:

| 10x=9x+19 | | 4(2z)=-72 | | 6x^2+54x=0 | | 2(x+3)(x-1)=x+176 | | x^3-0.9x^2-3.22x=0 | | -6a^2-7a+24=0 | | -5-4x=-13 | | -10m+6m=18-30 | | 2n=8n+21 | | 4+15r-3=9r+27-7r | | 3x-(5x+2)=9x-13 | | 5(4-2x)=100 | | w(w+4)=116 | | 0=-12n | | 8-12c=2 | | -4y^2+11y-6=0 | | r=-0.9233 | | 3t+5t=47+11-18 | | -5x+2+x+5=-5(x+2)+19 | | r^2=-0.923 | | 4x-5=6x+7 | | 6-6=4r-2r | | x^2-1.1x-2.76=0 | | -836=26y | | 7(-1+p)=-35 | | -4y+3=-3(2y+5) | | .60(z-300)+.05z=.70z-205 | | 7c^2-49c+70=0 | | 3s-12s=63 | | 2x^2+9=41 | | logx=2.0832 | | 9x-(3x+8)=7x-10 |

Equations solver categories